Intercultural Education as a Chance for the Integration of Refugee Children - Stanisława Nazaruk (Jesuit University Ignatianum in Krakow, 2014)
This article sheds light on the relevance of intercultural education for the integration of refugee children. Modern man has witnessed immense changes with the rise of globalization, migration, refugee emigration, all of which implicate the growth of national multi-ethnicity and associated issues of multi-cultural society. In order to avoid the conflicts resulting from societies' heterogeneous structure, each society requires an infusion of knowledge and education directed toward attitudes of openness to cultural differences. An important part of this process belongs to the Polish school system, not only in educating, but also upbringing. The author of this publication provides an example of intercultural education in practice, built on the experience of a small elementary school with Chechen refugee children. Highlighted in this example is the integration practice "step after step," aimed at strengthening ties and building positive relationships.  Artykuł przybliża istotę i znaczenie edukacji międzykulturowej w procesie integrowania dzieci uchodźców. Współczesny człowiek jest świadkiem zachodzących i nieuniknionych  zmian typu: globalizacja, migracja, uchodźstwo, które implikują wzrastającą liczbę wieloetniczności państw i z tym związane problemy wielokulturowości. Aby zapobiec konfliktom wynikającym ze struktury heterogenicznych społeczeństw, należy upowszechniać wiedzę i edukować społeczeństwo w kierunku postaw otwartości wobec odmienności kulturowych. Istotne zadanie w wymienionym procesie ma do wykonania Polska szkoła, nie tylko w obszarze edukacji, ale i wychowania. Autorka artykułu podaje przykład realizacji edukacji międzykulturowej w praktyce na przykładzie małej szkoły podstawowej, w której uczą się dzieci uchodźców z Czeczenii. Szczególnie mocno został podkreślony sposób integrowania ,,krok po kroku", który utrwala więzi i buduje pozytywne relacje.